Growth surveillance in the context of the Primary Public Healthcare Service Network in Brazil: literature review - Dixis Figueroa Pedraza (Instituto Materno Infantil de Pernambuco, 2016)
Abstract Objectives: to identify and analyze the scientific literature on child growth monitoring in the context of the primary public healthcare service network in Brazil, focusing on the main problems detected in studies. Methods: the review was based on searches ofSciELO, Lilacs and PubMed databases to identify articles published between 2006 and 2014. The articles were categorized according to the analytical categories of structure (items needed to carry out primary activities) or work processes (set of activities and procedures used in the management of resources). Results: of the 16 articles included in this review, only six dealt with structure and, in these, thetraining of professionals and availability of protocols were the most frequently identified problems. Processes, addressed in 15 articles, highlighted the underutilization of Child Health Handbook to record growth measurements and the adoption of guidelines on the basis of notes taken. Conclusions: the difficulties found demonstrate the everyday circumstances of the public health service which have a detrimental effect on growth surveillance.